Avaliação dos parâmetros físico-químicos do sal obtido na empresa refimosal e desenvolvimento do sal hipossódico (sal light) - Lima, Sayonara Vanessa de Medeiros (Universidade Federal Rural do Semi-Árido, 2017)
The purpose of this study is to present the activities carried out during the supervised training period at the REFIMOSAL (Refining and Grinding of Sal Santa Helena LTDA), located in the municipality of Mossoró / RN, which buys the salt in natura to benefit it According to the customer's need. During the stage, the process of beneficiation of the salt was followed, which comprises the following steps. Grinding and refining the salt. Physical-chemical analyzes were also carried out to verify that the product is in specifications that meet the standards established by ANVISA - National Agency for Sanitary Surveillance. The analyzes performed comprise: iodine percentage (KIO3); Percentage of calcium (Ca+2) and magnesium (Mg+2); Percentage of sulfates (SO4); Percentage of sodium ferrocyanide (Na4Fe(CN)6); granulometry; Insoluble residues and moisture. In addition, a new formulation was developed for the light salt (sodium salt), which presents low sodium contents, in the range of 50 to 70% of potassium chloride in its formulation.
Monografia
Keywords: Cloreto de sódio; Análises físico-químicas; REFIMOSAL; Cloreto de potássio; Sal light; Sodium Chloride; Physicochemical analysis; Potassium chloride; ENGENHEARIAS::ENGENHARIA QUIMICA